Strategy For Achieve National Education Standards at Madrasah Aliyah Negeri 1 Langkat - Rosadi, Edy; Mukti, Abd.; Siahaan, Amiruddin (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The purpose of this research is to find out: 1) Organizational ranks in identifying problems related to National Education Standards at Madrasah Aliyah Negeri 1 Langkat; 2) Organizational ranks in formulating strategic targets related to National Education Standards at Madrasah Aliyah Negeri 1 Langkat; 3) Strategic planning in achieving National Education Standards at Madrasah Aliyah Negeri 1 Langkat; and 4) Strategic implementation steps in achieving National Education Standards at Madrasah Aliyah Negeri 1 Langkat. This research uses a qualitative approach with descriptive methods. Technique Data collection uses interview techniques, observation and document study, while strengthening validity uses credibility, transferability, dependability and comfirmability. The results of this research are: 1) The staff involved in identifying problems in meeting the National Education Standards (SNP) madrasa head, deputy madrasa head, SNP drafting team, teachers, and madrasa committee. The large number of elements or ranks involved in the process of identifying this problem shows that the madrasah has a work team, a strong culture of collaboration, commitment and dedication from the entire educational community, as well as support from the authorities and stakeholders related to this, thus helping the madrasah in improving quality of education in accordance with applicable National Education Standards; 2) The mechanism chosen by the ranks of Madrasah Aliyah Negeri 1 Langkat in formulating strategic targets related to fulfilling the SNP is carried out systematically and directed 3) Strategic planning at Madrasah Aliyah Negeri 1 Langkat can be effectively and efficiently directed at efforts to achieve compliance with national education standards and improve the quality of the education they offer. The strategic planning carried out begins with understanding the SNP, carrying out a madrasa SWOT analysis, forming a planning team, establishing a vision and mission, identifying strategic targets, analyzing resource needs; strategy development, formation of action plans, monitoring and evaluation, involvement of related parties, and commitment to continuous improvement; 4) The strategic implementation steps taken by Madrasah Aliyah Negeri 1 Langkat begin with building communication and counseling for all elements of the madrasah. This communication involves the entire madrasah community, including teachers, students, parents and other related parties, intended to ensure a deep understanding of the goals and benefits of achieving SNP, in addition to carrying out teacher training, implementing appropriate curricula, monitoring learning activities, developing human resources. , improving facilities and infrastructure, collaboration with external parties, regular evaluations, participation of students and parents, use of educational technology, continuous improvement, and systematic reporting to the central government or educational authorities